2018
DOI: 10.1080/20013078.2018.1555410
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation‐based extracellular vesicle isolation from rat plasma co‐precipitate vesicle‐free microRNAs

Abstract: The microRNA (miRNA) cargo contained in plasma extracellular vesicles (EVs) offers a relatively little explored source of biomarkers for brain diseases that can be obtained noninvasively. Methods to isolate EVs from plasma, however, are still being developed. For EV isolation, it is important to ensure the removal of vesicle-free miRNAs, which account for approximately two-thirds of plasma miRNAs. Membrane particle precipitation-based EV isolation is an appealing method because of the simple protocol and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 33 publications
5
69
0
Order By: Relevance
“…Interestingly, we observed that miR-142-3p was enriched in the plasma fractions associated with EVs, rather than proteins. This is in accordance with previous studies (1,21) and it has been shown that only a minor portion of circulating miRNAs are associated with EVs, whereas a majority of circulating miRNAs could be found as bound to Argonaute2 protein (1). EVs, containing miRNAs and mRNAs, have been hypothesized to be actively released by the cells and participate in intercellular communication (25,57).…”
Section: Circulating Mir142 and Mir155 In The Rat Plasma Post-tbisupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we observed that miR-142-3p was enriched in the plasma fractions associated with EVs, rather than proteins. This is in accordance with previous studies (1,21) and it has been shown that only a minor portion of circulating miRNAs are associated with EVs, whereas a majority of circulating miRNAs could be found as bound to Argonaute2 protein (1). EVs, containing miRNAs and mRNAs, have been hypothesized to be actively released by the cells and participate in intercellular communication (25,57).…”
Section: Circulating Mir142 and Mir155 In The Rat Plasma Post-tbisupporting
confidence: 92%
“…Size-exclusion chromatography (SEC) of plasma SEC analysis was performed as previously described (8,21). Briefly, plasma samples (200 µL) from four rats (two TBI, one sham and one naïve rat) were passed through sepharose CL-2B (GE Healthcare; Uppsala, Sweden) chromatography columns.…”
Section: Sample Collectionmentioning
confidence: 99%
“…These different RNA carriers overlap in size and buoyant density [59], which complicates strict separation of the different particles. The different types of EV isolation methods that are currently in use vary largely in the level of contamination with LPP and RNP [22,[74][75][76]. Moreover, the currently used RNA isolation kits exhibit variable recovery efficiencies for RNAs enclosed in each of the different macromolecular complexes (EV, LPP and RNP) [22].…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use affinity-based columns in our present study. Other EV isolation methods include ultracentrifugation, which requires high volumes of (pooled) samples, and precipitation, which does not exclude non-EV miRs from serum ( Karttunen et al, 2018 ). As the aim was to compare the serum and sweat EV-miR populations, affinity-based columns were the most promising tool for our setup ( Enderle et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%